1998
DOI: 10.1093/brain/121.4.755
|View full text |Cite
|
Sign up to set email alerts
|

The reaching movements of patients with Parkinson's disease under self- determined maximal speed and visually cued conditions

Abstract: Two-dimensional kinematic analysis was performed of the reaching movements that six subjects with Parkinson's disease and six healthy subjects produced under self-determined maximal speed and visually cued conditions. Subjects were required to reach as fast as possible to grasp a ball (i) that was fixed stationary in the centre of a designated contact zone on an inclined ramp (self-determined maximal speed condition), or (ii) that rolled rapidly from left to right down the incline and into the contact zone (vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
116
1
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(141 citation statements)
references
References 59 publications
12
116
1
2
Order By: Relevance
“…Means standard errors, and F values of the kinematic measures are shown in Table 2. In agreement with numerous studies that reported bradykinetic movements in PD patients (Alberts et al 2000;Castiello et al 1999;Majsak et al 1998;Tresilian et al 1997), the PD patients produced significantly slower transport movements than controls (P<0.05). As for the grasp component, PD group had a significantly smaller amplitude of maximum grip aperture than controls (P<0.001), showing the hypometric movement features that are typical for individuals with PD (Castiello and Bennett 1994;Castiello et al 1999;Gentilucci and Negrotti 1999).…”
Section: Parameters Relating To Aperture Closure Initiationsupporting
confidence: 92%
See 1 more Smart Citation
“…Means standard errors, and F values of the kinematic measures are shown in Table 2. In agreement with numerous studies that reported bradykinetic movements in PD patients (Alberts et al 2000;Castiello et al 1999;Majsak et al 1998;Tresilian et al 1997), the PD patients produced significantly slower transport movements than controls (P<0.05). As for the grasp component, PD group had a significantly smaller amplitude of maximum grip aperture than controls (P<0.001), showing the hypometric movement features that are typical for individuals with PD (Castiello and Bennett 1994;Castiello et al 1999;Gentilucci and Negrotti 1999).…”
Section: Parameters Relating To Aperture Closure Initiationsupporting
confidence: 92%
“…Since the PD patients exhibited a smaller grip aperture and moved their hand significantly more slowly than the control subjects, the control law predicts that the distance to target at which they initiated aperture closure should also be shorter. Thus, the shorter aperture closure distance observed in PD patients can be viewed as resulting from hypometria of their grip aperture (Castiello and Bennett 1994;Castiello et al 1999;Gentilucci and Negrotti 1999) and bradykinesia of their hand transport (Alberts et al 2000;Castiello et al 1999;Majsak et al 1998;Tresilian et al 1997), rather than being a result of a deficit in transport-grip coordination in terms of the initiation of aperture closure.…”
Section: Discussionmentioning
confidence: 99%
“…The current study was able to rule out this hypothesis by testing participants in a passive motion condition (i.e., pushed in a wheelchair) as well as in virtual reality where visual motion was simulated without vestibular information. During passive motion (wheelchair condition), both groups did not differ in judgment accuracy demonstrating that when all other sensory cues are available, and proprioception is limited, PD patients are able to estimate distance with motion as accurately as healthy control 30 participants suggesting perhaps that visual motion stimuli engage neural circuits that are less affected by PD (Majsak, Kaminski, Gentile, & Flanagan, 1998;Majsak, Kaminski, Gentile, & Gordon, 2008).…”
Section: Perception Of Distance With and Without Movementmentioning
confidence: 99%
“…It occurs, for example, when a patient with symptoms of akinesia and bradykinesia responds to an alarm by walking rapidly away from the scene. Several studies support these clinical observations, documenting that the ability of patients with PD to begin a motor sequence is more severely impaired (in terms of response times) when they have to rely on self-determined mechanisms than when the drive to act is triggered by an external cue (Jahanshahi et al, 1995;Majsak et al, 1998;Siegert et al, 2002). Overall, these findings are fairly consistent with our finding of a selective impairment after L-dopa withdrawal in the component of the task that specifically requires the subject to self-activate the intention to perform the actions.…”
mentioning
confidence: 96%
“…A parallel could be drawn between the deficit in self initiating the prospective intention and the phenomenon of "akinesia paradoxica" held to be characteristic of PD (Jahanshahi et al, 1995;Majsak et al, 1998;Siegert et al, 2002; but see Ballanger et al, 2006, for partially divergent view). This term refers to the fact that PD patients can often initiate movements more quickly in response to external stimuli than voluntarily.…”
mentioning
confidence: 97%